2009
DOI: 10.1111/j.1538-7836.2009.03589.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin but not citrate anticoagulation of blood preserves platelet function for prolonged periods

Abstract: To cite this article: Truss NJ, Armstrong PCJ, Liverani E, Vojnovic I, Warner TD. Heparin but not citrate anticoagulation of blood preserves platelet function for prolonged periods. J Thromb Haemost 2009; 7: 1897-905.Summary. Background: Current guidelines state that platelet aggregation studies should be conducted within 4 h of venepuncture because of the decline in sensitivity to platelet agonists. This constrains studies of platelet activity in clinical situations where samples need to be transported or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
4
22
0
1
Order By: Relevance
“…There were no significant differences in aggregability between the direct thrombin inhibitor samples and heparin samples, whereas the aggregation in citrated samples after stimulation from most of the agonists was impaired [168]. This finding is in accordance with several studies and supports the recommendation to apply hirudin in preference to citrate anti-coagulated samples [53,165,169].…”
Section: Impedance Aggregometrysupporting
confidence: 89%
See 1 more Smart Citation
“…There were no significant differences in aggregability between the direct thrombin inhibitor samples and heparin samples, whereas the aggregation in citrated samples after stimulation from most of the agonists was impaired [168]. This finding is in accordance with several studies and supports the recommendation to apply hirudin in preference to citrate anti-coagulated samples [53,165,169].…”
Section: Impedance Aggregometrysupporting
confidence: 89%
“…Nevertheless, the application of citrated blood for platelet function tests is controversial since the Ca 2+ -binding properties of citrate create a non-physiological milieu in which the platelets are suspended [163,164]. Direct comparisons of citrate and heparin anti-coagulated samples using LTA as well as impedance aggregometry revealed that, as measured with both methods, the platelet function was impaired in citrate anti-coagulated samples after 24 h, whereas platelet function in heparin anti-coagulated blood was predominantly preserved [165]. However, other authors state that heparin is unsatisfactory due to in vitro platelet clumping and platelet adherence to the sampling device, resulting in low platelet numbers in PRP [166].…”
Section: Impedance Aggregometrymentioning
confidence: 99%
“…Possibly it is one of a reasons some authors report the use of heparin as an effective anticoagulant for PRP preparation [27,28]. Heparin was also shown to preserve platelet function for a longer time than SC [29]. Yet most studies show heparin activates platelets [30].…”
Section: Resultsmentioning
confidence: 99%
“…The search for an ideal anticoagulant for blood samples used for the quantification of platelet function is still ongoing. Heparin will be the anticoagulant used in the present study [16,17]. Blood will be collected in 4 ml heparin (Lithium Heparin 68 IU)-coated BD Vacutainer plastic tubes.…”
Section: Methodsmentioning
confidence: 99%